GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU SD NEGERI 10 BANDAR BARU - Saputri, Mutia; Marwan, Marwan; Mulyadi, Said (Jurnal Manajemen Pendidikan, 2025)
In managing and leading a school, a principal must possess competence. Competence refers to the combination of knowledge, attitudes, and skills required in school leadership and management. A principal's leadership style is the approach or method used to lead, influence, and direct all school members—especially teachers—in achieving educational goals. Each principal exhibits a different leadership style, influenced by their personality, educational background, experience, and the socio-cultural environment in which they operate. This study aims to identify the leadership style of the principal of SD Negeri 10 Bandar Baru in enhancing teacher performance. A descriptive method with a qualitative approach was employed in this research. Data were collected through interviews, observations, and documentation. The data analysis followed an inductive approach, consisting of data reduction, data display, and conclusion drawing. The research subjects were the school principal and the teachers. The findings revealed the following: 1) The transformational leadership style is effectively applied at SD Negeri 10 Bandar Baru. 2) This leadership style has successfully contributed to improved teacher performance. 3? Supervision of teaching administration is conducted regularly, with the results documented and utilized as evaluation material within the school.